Acute limb ischemia as presentation of pediatric antiphospholipid syndrome: case report - Ana Dias-Curado; Carolina Amaro-Gonçalves; Maria João-Palaré; Filipa Oliveira-Ramos; Anabela Ferrão (Publicaciones Permanyer, 2023)
Antiphospholipid syndrome (APS) is an autoimmune systemic disorder characterized by an increased risk of thrombosis and the presence of circulating antiphospholipid antibodies (aPL). A previously healthy 7-year-old girl was admitted complaining of right leg and foot pain with claudication. She had a malar rash, pallor and cooling of the limb, cyanosis of the toes and non-palpable popliteal and distal pulses. The vascular doppler showed a right popliteal artery occlusion and she started enoxaparin. Laboratory studies showed positive Coombs test, triple positive aPL, positive antinuclear and anti-double stranded DNA antibodies, C4 mild consumption. She started hydroxychloroquine, acetylsalicylic acid and warfarin, with posterior suspension of enoxaparin. Diagnosis of APS was confirmed 12 weeks later as aPL remained positive. There was a good clinical evolution with signs of re-vascularization. APS is rare in the pediatric population and has a wide clinical spectrum, becoming a diagnostic and therapeutic challenge due to the small number of pediatric studies.